DIGITAL OR NOT DIGITAL? KEY FACTORS AND BENEFITS OF SMEs’ TRANSFORMATION: A SYSTEMATIC LITERATURE REVIEW - Hanim Nazira Zulkipli; Norazlina Ilias; Wan Zuriati Wan Zakaria, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2025)
Within the contemporary corporate landscape, the digital transformation process has emerged as a crucial facilitator for organizations' long-term viability and competitive advantage Although bigger organizations have readily adopted digital technology, small, and medium-sized enterprises (SMEs) must carefully evaluate certain variables and understand the benefits of implementing digital transformation efforts. This systematic review aims to provide a thorough and inclusive examination of the elements SMEs consider as they embark on their digital transformation path. The analysis of 418 Web of Science (WoS) and Scopus-indexed articles published between 2014 and 2024 served as the basis for this review. The results suggest that the elements influencing the adoption of digital transformation include environmental, organizational, and technological aspects. One of the key benefits related to adopting digital transformation for SMEs is the potential reduction in operational costs. This study undertakes a comprehensive examination and evaluation of scholarly literature to identify significant subjects and gather data that will influence future research and practical strategies for SMEs aiming to thrive in the digital realm.